فکر اقبال میں واقعات کربلا کے حماسائی پہلوؤں کا توضیحی مطالعہ: The epic elements of the incident of Karbala in Iqbal's thought: A research study - Batool, Rida (Tashkeel e Jadeed, 2025)
The immortal sacrifice of Imam Hussain (AS) and his companions in the Karbala incident have had an impact on every aspect of life. The effects of the Karbala incident are also clearly visible in the fine arts, especially in Urdu and Persian poetry, where this incident has been made a topic in many cases. However, if we look at the history of Urdu, Persian and especially Urdu poetry, we see the description of the Karbala incident as grief and sorrow. Most of the poets have made the martyrdom of Imam Hussain (AS) a topic that creates a feeling of weeping. The genre of elegy (مرثیہ) has become famous for this purpose. In Urdu ghazals, poems and prose, there is a lesson of truth and honesty from this incident, but the aspect of courage that inspires one to stand up against the oppressor is not seen. In the Urdu poetic tradition, Iqbal is the only poet who has presented the incident of Karbala as an ideology that comes to the fore as a symbol of courage, bravery and valor. In Iqbal's Urdu-Persian poetry, except for one or two places in Matrook Kalam, the mention of Imam Hussain (AS) and Karbala is nowhere in the sense of weeping. He has presented Karbala as an epic that teaches lessons of perseverance and courage. Iqbal wanted to adapt the events of Karbala in poetry as a response to Milton's Paradise Lost, but he did not get this opportunity. However, he has described the events of Karbala in his poetry as an epic, and this is his uniqueness in describing the events of Karbala in Urdu literature.